Electromagnetic Compatibility Studies: LTE BS vs. Aeronautical Radionavigation Services in 694-790 MHz Frequency Band - Stankevičius, Evaldas; Oberauskas, Šarūnas (Electrical, Control and Communication Engineering, 2014)
This paper presents the sharing analysis of the 694–790 MHz frequency band for Mobile services IMT and Aeronautical radio-navigation services (ARNS) using SEAMCAT (established by CEPT) software based on the statistical simulation (Monte-Carlo) method. In 2012 the World Radiocommunication Conference (WRC-12) decided to allocate the 694–790 MHz frequency band (the so-called 700 MHz band) to mobile services IMT (excluding aeronautical mobile) after WRC-15 conference. But this agreement raises electromagnetic compatibility problems, which should be solved until WRC-15 [1]. This study was carried out in two phases: first applying theoretical analysis, then statistical Monte-Carlo simulations with SEAMCAT software tool in order to verify results obtained in theoretical approach. Analytical calculations shows that the required protection distances between ARNS stations and the MS base stations are 132 km. The obtained results from SEAMCAT simulations indicate that separation distance should be above 100 km. These results illustrate that the systems are not electromagnetically compatible. The possible mitigation technic could be antenna pattern correction.